Estado nutricional en escolares chilenos según la referencia NCHS y OMS 2007 Nutritional status in Chilean school children according to NCHS and WHO 2007 reference - E. Atalah Samur; S. Loaiza; M. Taibo (Nutrición Hospitalaria, 2012)
Antecedentes: El 2007 la OMS publicó una nueva referencia para evaluar el estado nutricional en niños y adolescentes de 5 a 19 años, que incluye tablas de índice de masa corporal (IMC) por edad y sexo. Objetivo: Análisis comparativo del estado nutricional según IMC en escolares y adolescentes chilenos utilizando la norma vigente del Ministerio de Salud (NCHS) y la nueva referencia OMS 2007. Material y métodos: Cohorte retrospectiva de 117.745 recién nacidos, con evaluación nutricional al ingresar a educación básica (1997) y enseñanza media (2005). Se analizó el estado nutricional según IMC en relación a las referencias NCHS 1977, OMS 2007 en desviaciones estándar (DE) y en percentiles. Se evaluó la concordancia diagnóstica según los tres criterios con el índice Kappa. Resultados: Hubo pocas diferencias en la clasificación nutricional en primero básico (6,4 ± 0,3 años) entre los tres criterios. En primero medio (14,4 ± 0,3 años) fue mayor la prevalencia de bajo peso con ambas referencias OMS, de sobrepeso con OMS DE y de obesidad con OMS percentiles (p < 0,001). La principal diferencia estuvo en la clasificación de obesidad (≥ percentil 95), donde el 43,9% de los obesos por OMS percentiles fue clasificado sobrepeso con NCHS (concordancia 87,3% Kappa 0,75). Conclusiones: Hubo una concordancia diagnóstica cercana al 90% entre los tres criterios. Existen algunas diferencias entre NCHS y OMS, así como entre las dos referencias OMS, dependiendo del punto de corte utilizado. La adopción de una u otra referencia debiera depender de los riesgos biológicos asociados. Background: In 2007, WHO published a new reference for assessing the nutritional status of children and adolescents aged 5 to 19 years, including body mass index (BMI) by sex and age. Objective: To compare the nutritional assessment by BMI in schoolchildren and adolescents using the actual Chilean Ministry of Health norm (NCHS) and the new WHO reference 2007. Material and methods: Retrospective cohort study of 117,745 newborns, with nutritional assessment on first year of basic education (1997) and later in high education (2005). We analyzed the nutritional status according to BMI for age in relation to the NCHS references and WHO 2007, in standard deviations (SD) and percentiles. We analyzed the agreement between the different references with the Kappa index. Results: There were small differences in the nutritional classification in first grade (6,4 ± 0,3 years) between the three references. Underweight prevalence was slightly higher with both WHO references, overweight with WHO in standard deviation and obesity with WHO percentiles, at first grade of high school (14,4 ± 0,3 years). The main difference was in relation to classification of obesity (≥ percentile 95), where 43,9% of obese by WHO percentiles were considered overweight with NCHS (87,3% concordance Kappa 0,75). Conclusions: The diagnostic concordance between the three criteria was the order of 90%. There are some differences between NCHS and WHO, and between both WHO reference, depending on the cutoff point used. The adoption of one or other reference should depend on the biological hazards associated with it.